(untitled) (Gaceta Técnica, 2021)
Access to information in real time, as we are used to, puts us in front of the reality offered by science and technology, allowing several individuals or groups to formulate hypotheses about an event. It was thus, with what happened during the abrupt collapse of a building in the city of Miami recently, in that sense it was possible to observe a great variety of aspects approached in different ways, among which the media, the superficial, even the most complex stand out. of engineering, but above all, the ability of professionals, researchers, to make an explanation from the technical, structural and construction point of view must be observed, relating the microclimate, maintenance and finances of a company.